Neuropsychiatric features of Prader–Willi syndrome. Issue 5 (30th January 2022) - Shelkowitz, Emily; Gantz, Marie G.; Ridenour, Ty A.; Scheimann, Ann O.; Strong, Theresa; Bohonowych, Jessica; Duis, Jessica
Abstract: Prader–Willi syndrome (PWS) is a genetic disorder characterized by hypotonia and poor feeding in infancy which progresses to hyperphagia in early‐mid childhood, as well as developmental delays, a spectrum of behavioral and psychiatric concerns, endocrinopathies, orthopedic issues, and less commonly, seizures, sleep apnea, and narcolepsy with or without cataplexy. This study used data in the Global PWS Registry ( N = 893) to explore the onset and severity over time of the neuropsychiatric features reported in individuals with PWS and explored its associations with sleep disorders, seizures, and psychiatric symptoms. Results demonstrate that seizures are more common in the deletion subtype and that narcolepsy and cataplexy are more common in individuals who have sleep‐related seizures. Finally, this work shows that anxiety and compulsive behaviors are persistent features of PWS that may arise early in childhood, and that anxiety is associated with higher frequency of other comorbid psychiatric diagnoses. In conclusion, this study is one of the largest to date characterizing sleep disorders and neuropsychiatric characteristics of individuals with PWS and reports on the novel association between sleep disorders and seizures. This study is also one of the first to offer details on the nature of the progression of these features in individuals with PWS.